Efficiency Wage Hypothesis: The Case Study of Iran’s Manufacturing Industries - Samimi, Ahmad Jafari (Journal of Social and Development Sciences, 2011)
The purpose of this paper is to test the efficiency wage hypothesis for Iran’s manufacturing industries at the 4-digit aggregation level of ISIC classification, during 2001-2006. According to the efficiency wage hypothesis, it is logical for some firms to pay wages that are above the market wage. In some cases the mere fact that workers are paid more can make them more productive. In other words, efficiency wages would increase productivity and there is positive relationship between wages and productivity. In this paper, panel data technique has employed to examine the mentioned hypothesis. However, the obtained results contradict the efficiency wage hypothesis for Iran’s manufacturing industries. In other words, according to this result, higher wages lead to less efficient performance by the workers of Iran’s manufacturing industries.